Students’ Perspective of Acceptable Online Learning Platforms for Japanese Language Skills Courses - Aji Setyanto; Efrizal Efrizal; Yohanes Padmo Adi Nugroho (STAI Hubbulwathan Duri, 2023)
This study aimed to determine which online learning platforms are suitable for Japanese language skills courses. By finding out the platforms, we were able to know which platforms were acceptable and unacceptable, as well as the primary factors and reasons behind them. Qualitative research was conducted to perform the study using open-ended questions and in-depth interviews. Interviews were conducted with first and second-year 132 Japanese language learners at one of the State University in Malang, Indonesia. Qualitative Data Analysis (QDA) software was used for data analysis to discuss, conclude and present in a structured manner. The results showed that the platforms used were acceptable because they were effective and efficient, easy to use, easy to understand the material, and in accordance with the learning character. Meanwhile, some platforms were declared unacceptable because trouble often occurred, less able to accept the material, difficult to interact with, challenging to use, and so on. The online platforms declared acceptable for Japanese language skills courses were Google Classroom, Google Form, Google Meet, Zoom Cloud Meeting, and WhatsApp Group (WAG). Especially for the Kaiwa and Choukai courses, apart from the platforms, Discord was also used. This study can be a reference for Japanese Language Instructure to choose the ideal platform to teach Japanese Language Skills in Online Classes.